Characterization of tanning behavior assessed via online survey: Attitudes, habits, and preventive measures with focus on sunscreen use - Schneiderbanger, Constanze K.; Schuler, Gerold; Heinzerling, Lucie; Kirchberger, Michael C. (Photodermatology Photoimmunology & Photomedicine, 2019)
Background/purpose: Incidence of melanoma is increasing globally. Exposure to ultraviolet radiation (UVR) as important risk factor for developing skin cancer can be influenced by tanning behavior. Only a few studies are available concerning sun tanning behavior and protective measures. Methods: An online survey was distributed via social media to assess tanning habits and examine associated demographic and behavioral factors. Results: In total, 403 questionnaires were distributed, and mean age of respondents was 32. Having a tanned skin, feeling warm and relaxed were the most common motivations for tanning. The use of sunscreen varied and seemed to depend on the occasion of UVR exposure, constantly applied during vacation and during tanning, less commonly applied in daily life and during work. Avoiding painful solar dermatitis was more important as motivation for the use of sunscreen than skin cancer prevention. Skin aging as reason for the use of sunscreen was especially important for females younger than 26 years. The most common applied sun protection factor was 16-49. The main reason opposing the use of sunscreen was a too laborious usage, which was significantly associated with male. Beauty was the only association related to tanned skin the majority (62%) agreed with. Conclusion: The motivation for tanning and reasons for avoiding sunscreen strongly varies. Knowledge about these factors could be used for improving campaigns with respect to target groups. Clarifying the appropriate application of sunscreen, developing convenient sunscreen formulations and providing information about UVR-induced skin aging could lead to an increased usage of sunscreen and therefore to an improved UVR protection.
CRIS-Team Scopus Importer:2019-07-30
Keywords: melanoma; sunscreen; tanning; ultraviolet radiation